Serum S100A12 levels: Possible association with skin sclerosis and interstitial lung disease in systemic sclerosis. Issue 3 (29th October 2020) - Omatsu, Jun; Saigusa, Ryosuke; Miyagawa, Takuya; Fukui, Yuki; Toyama, Satoshi; Awaji, Kentaro; Ikawa, Tetsuya; Norimatsu, Yuta; Yoshizaki, Ayumi; Sato, Shinichi; Asano, Yoshihide
Abstract: Damage‐associated molecular patterns (DAMPs) have drawn much attention as a member of disease‐associated molecules in systemic sclerosis (SSc). In this study, we investigated the potential contribution of S100A12, a member of DAMPs, to the development of SSc by evaluating S100A12 expression in the lesional skin and the clinical correlation of serum S100A12 levels. S100A12 expression was markedly elevated in the epidermis of SSc‐involved skin at protein levels and in the bulk skin at mRNA levels. The deficiency of transcription factor Fli1, a predisposing factor of SSc, enhanced S100A12 expression and Fli1 occupied the S100A12 promoter in normal human keratinocytes. Serum S100A12 levels were higher in SSc patients, especially in those with diffuse cutaneous involvement, than in healthy controls and positively correlated with skin score. Furthermore, the presence of interstitial lung disease significantly augmented serum levels of S100A12. Importantly, serum S100A12 levels correlated inversely with both per cent forced vital capacity and per cent diffusing capacity for carbon monoxide and positively with serum levels of KL‐6 and surfactant protein‐D. Collectively, these results indicate a possible contribution of S100A12 to skin sclerosis and interstitial lung disease associated with SSc, further supporting the critical roles of DAMPs in the pathogenesis of this disease.